Alocação de tráfego em redes ópticas em anel com proteção - Haroldo do O. Carvalho (2007)
This work report presents the application of a Linear Programming model to an optical SDH (Synchronous Digital Hierarchy) network which employs the SNC-P (Subnetwork Connection Protection) protection scheme, in order to optimize the routing of the carriedout traffic. The model was described through the AMPL software and solved on the commercial package Cplex1. Different tests in relationship with network topology and traffic profile were performed. The model represents the technological characteristics of a SDH network configured in rings, with ADM (Add-Drop Multiplex) elements. Several tests were made, considering different traffic conditions, in order to evaluate the quality of the solutions obtained with the use of the adopted computing tool.The traffic optimization problem aimed by this paper has a combinatory nature and is characterized as a NP-complete problem. It is worth to note that, for certain network dimensions, the presence of integer variablesin the model demands the employment of machine-time reducing heuristics, which are not in the scope of this work. So that, the computational tests results indicated that the model developed is better fitted to networks configured with no more than 8 (eight) nodes